2019
DOI: 10.3390/ijerph16030305
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Impairment among Patients with Different Skin Diseases in Vietnam: A Cross-Sectional Study

Abstract: Skin diseases have caused a heavy burden on the infected population worldwide. This study aimed to examine the health-related quality of life (HRQOL) among patients with different skin diseases and identify associated factors. A cross-sectional study with 430 participants was conducted at the Vietnam National Hospital of Dermatology and Venereology (NHD) from September to November 2018. The EuroQol-5 Dimensions-5 Levels (EQ-5D-5L) instrument was employed, which measures the EQ-5D index from five domains includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 42 publications
3
34
0
2
Order By: Relevance
“…A study from Cyprus reported a significantly higher score (0.97) among hypertensive patients. 22 The overall EQ-5D score for hypertensive patients (0.732) in this study was lower than Asian patients suffering from diabetes (0.8) 23 human immunodeficiency virus (0.8) 24 ; similar to skin diseases (0.73) 25 but higher than respiratory diseases (0.66), 26 dengue fever (0.66), 27 frail elderly (0.58) 28 and elderly after fall injury (0.46 34 Barsky et al, reported that hypertensive women tend to report somatic symptoms more frequently than men, such symptoms are reportedly of greater intensity compared with men. 35 Similar to our finding, higher annual household income has been associated with better HRQoL.…”
Section: Discussionmentioning
confidence: 61%
“…A study from Cyprus reported a significantly higher score (0.97) among hypertensive patients. 22 The overall EQ-5D score for hypertensive patients (0.732) in this study was lower than Asian patients suffering from diabetes (0.8) 23 human immunodeficiency virus (0.8) 24 ; similar to skin diseases (0.73) 25 but higher than respiratory diseases (0.66), 26 dengue fever (0.66), 27 frail elderly (0.58) 28 and elderly after fall injury (0.46 34 Barsky et al, reported that hypertensive women tend to report somatic symptoms more frequently than men, such symptoms are reportedly of greater intensity compared with men. 35 Similar to our finding, higher annual household income has been associated with better HRQoL.…”
Section: Discussionmentioning
confidence: 61%
“…The majority of FCs indicated that they completely (50.5%) or partially (46.9%) understood the patient's disease. The median (IQR) number of hours of caregiving per day was 20 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). Table 1 shows the QOL of AL patients and FCs.…”
Section: Participants' Characteristicsmentioning
confidence: 99%
“…It is recommended that health-related QOL is evaluated along with clinical and laboratory indicators [11]. Evaluating health-related QOL informs an integral part of treatment effectiveness [12] and burden of disease [13].…”
mentioning
confidence: 99%
“…Patients selecting the option "no problem" was classified into the "No problem" group; otherwise, they were classified into the "Having problem" group. This tool has been widely used in Vietnam [37][38][39][40][41][42]. Moreover, we utilized the EQ-Visual Analogue Scale (EQ-VAS) to measure current self-rated health, with a score ranging from 0 "The worse health state that you can imagine" to 100 "The best health state that you can imagine".…”
Section: Health-related Quality Of Lifementioning
confidence: 99%